Organic Synthesis Enabled by Light-Irradiation of EDA Complexes: Theoretical Background and Synthetic Applications - Lima, Carolina G. S; de M. Lima, Thiago; Duarte, Marcelo; Jurberg, Igor D; Paixão, Márcio W (ACS catalysis, 2016)
In the past decades, the physicochemical properties of electron donor–acceptor, EDA, complexes (also called charge-transfer, CT, complexes) have been extensively studied, although their synthetic applications have been somewhat limited. However, in recent years, this scenario has started to change as an increasing number of examples have been reported. In this regard, this review aims to present and discuss the main aspects associated with the physicochemical properties of these complexes and a selection of synthetic photochemical applications in organic chemistry.